2012
DOI: 10.1177/0748233711432573
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of Butea monosperma on vincristine-induced neuropathic pain model in rats

Abstract: Neuropathic pain is a chronic neurodegenerative disease. It is well characterized by spontaneous pain, hyperalgesia, hypothesia, dysesthesia and allodynia. The present study was designed to investigate the antinociceptive potential of Butea monosperma on vincristine-induced painful neuropathy in rats. Vincristine was administered for induction of neuropathic pain in experimental animals. Hot plate, acetone drop, paw pressure, Von Frey hair and tail immersion tests were performed to assess the degree of thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…21,22 Concentrations of thiobarbituric acid reactive substances (TBARS) and superoxide anions were increased by vincristine treatment. 23,24 It has been reported that lipoic acid treatment reversed indices of oxidative stress, Table 1. Effect of intraperitoneal injection with normal saline or thioctic acid on mechanical allodynia withdrawal threshold in vincristine-induced neuropathy in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Concentrations of thiobarbituric acid reactive substances (TBARS) and superoxide anions were increased by vincristine treatment. 23,24 It has been reported that lipoic acid treatment reversed indices of oxidative stress, Table 1. Effect of intraperitoneal injection with normal saline or thioctic acid on mechanical allodynia withdrawal threshold in vincristine-induced neuropathy in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Oral intake of ethanolic extract of B. monosperma (200-400 mg/kg for 14 days) suppressed histological, biochemical, and behavioral changes induced by vincristine in rats. Authors have suggested that the therapeutic benefits might originate from its calcium channel inactivating, anti-oxidative, anti-inflammatory, and neuroprotective effects [29].…”
Section: Butea Monospermamentioning
confidence: 99%
“…An imbalance in the diet can lead to malnutrition; eating low amounts of certain nutrients can lead to deficiencies while eating too much can lead to toxicities. The elemental distribution in BM was compared to Dietary Reference Intakes (DRIs) (TABLE [5][6][7][8][9][10][11]. If an average serving size of 10 g (dry mass) of BM is consumed it would contribute significantly towards the daily intake of important nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The plant has proven efficacy for antioxidant [5] anti-obesity [6] anticancer, and chemoprotective [7] potential. It is also useful against neuropathic [8] and peripheral pain.…”
mentioning
confidence: 99%